EFFECT OF BUILDING FORM WITH INNER COURT AND HEIGHT VARIATIONS ON THERMAL COMFORT OUTDOOR SPACE IN SUDIRMAN SUITES APARTMENT BANDUNG - Hamdani (Jurnal Riset Arsitektur, 2019)
Abstract- Designing apartment as a vertical residence should not only pay attention to aesthetics value but also aspects comfort aspects, such as thermal comfort. Apartment thermal comfort is not only limited to indoor units but also outdoor space as residents’ communal area. Sudirman Suites Apartment built in the center of Bandung City with limited land availability is selected as the research object because of the uniqueness of the building form with inner court and height variation that allows the availability of outdoor space on the floor above. Sudirman Suite Apartments’ building form and height can affect the site’s microclimate and outdoor space thermal comfort. This study aims to determine the effect of building form with inner court and height variation to thermal comfort of apartment outdoor space as well as the right solution to improve it.  This study used quantitative method, with descriptive evaluative type of research. Measurements were taken on the Sudirman Suite Apartment outdoor space such as ground floor parking area, terrace, and aisle, 1st floor inner court, 2nd floor roof garden, and sky garden on 9th and 11th floor. The measurement data then calculated into thermal comfort perception and analyzed based on theories of literature study result to reach conclusion. Influence of the building form and height to outdoor space thermal comfort the thermal comfort of Sudirman Suites Apartment analysis divided into: outdoor space on the main mass with inner court and height variations, pilotis on the ground floor of the main mass, and supporting mass addition. Besides of the building form and height, environmental factors also affect the outdoor space thermal comfort such as wind and radiative temperatures in each outdoor space. Based on this study, it is known that there is significant effect of the apartment’s form with inner court, where the comparison between blocking tower height and comparable distance between towers makes inner court area air flow tend to be low. Pilotis on the ground floor increases the speed of air flow on the ground floor. Sun radiation reduction occurs in the sky garden area overshadowed by building form with height variation. Outdoor space elements optimization is considered less optimal in supporting thermal comfort, such as the lack of plants and rooftop surface area dominated by hardscape.  Key Words: apartment, outdoor space, thermal comfort, Bandung Sudirman Suites